2020
DOI: 10.3390/gels6040041
|View full text |Cite
|
Sign up to set email alerts
|

Role of N–Oxide Moieties in Tuning Supramolecular Gel-State Properties

Abstract: The role of specific interactions in the self-assembly process of low molecular weight gelators (LMWGs) was studied by altering the nonbonding interactions responsible for gel formation via structural modification of the gelator/nongelator. This was achieved by modifying pyridyl moieties of bis(pyridyl) urea-based hydrogelator (4–BPU) and the isomer (3–BPU) to pyridyl N–oxide compounds (L1 and L2, respectively). The modification of the functional groups resulted in the tuning of the gelation properties of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Apart from interactions in and between the gelator molecules, static QM calculations can be used to gain information on the strength and nature of explicit interactions between the gelator and an additive or the solvent [ 40 , 43 ]. In a collaborative effort of the Rai and Kundu groups, a variety of structures of a solvent molecule and a di-Fmoc- L -lysine gelator were optimized at the DFT level of theory [ 44 ].…”
Section: Rationalizing Supramolecular Gelationmentioning
confidence: 99%
“…Apart from interactions in and between the gelator molecules, static QM calculations can be used to gain information on the strength and nature of explicit interactions between the gelator and an additive or the solvent [ 40 , 43 ]. In a collaborative effort of the Rai and Kundu groups, a variety of structures of a solvent molecule and a di-Fmoc- L -lysine gelator were optimized at the DFT level of theory [ 44 ].…”
Section: Rationalizing Supramolecular Gelationmentioning
confidence: 99%
“…The modification of the pyridyl functionality in pyridyl urea-based compounds could alter the N-H• • • N interactions to N-H• • • O interactions. Recently, we have shown that modifying pyridyl groups to the corresponding pyridyl-N-oxides [30] can restore the N-H• • • O interactions, leading to enhanced gelation ability. In this work, we have selected bis(pyridyl urea)-based compounds (3-HBU [29], 3-BBU [48], 4-HBU, and 4-BBU; see Scheme 1) as the parent compounds.…”
Section: Design and Synthesismentioning
confidence: 99%
“…The presence of pyridyl/pyridyl-N-oxide moieties in our compounds makes them ideal candidates as stimuli-responsive soft materials because these groups are known to interact with the salts/ions. We have previously reported the anion sensing studies of pyridyl-N-oxide compounds [30] and have shown that gel-sol transition can be used to detect cyanide ions [60]. This prompted us to explore the effect of salts in the gelation properties of bis(pyridyl urea) and its corresponding bis(pyridyl-N-oxide urea) compounds.…”
Section: Physical Properties In the Presence Of Saltsmentioning
confidence: 99%
See 2 more Smart Citations